Eksistensi Kuliner Pempek sebagai Icon Kota Palembang (Studi Sejarah dan Budaya) - syarifuddin,; Arfilla, Dinda; Fadilla, (Rihlah: Jurnal Sejarah dan Kebudayaan, 2022)
One form of local wisdom in Palembang is the culinary. The most famous culinary in the Palembang city is pempek. Pempek culinary can be used as the identity of the Palembang city. Pempek Palembang has great potential for culinary business and must be preserved. Pempek Palembang is very famous for its specialties, with the basic ingredients for making it are fish meat and sago which are in accordance with the natural resources that exist in the city of Palembang. Pempek Palembang is served with a black sauce known as cuko. Pempek culinary as Palembang icon can be seen from the existence of the pempek culinary where the pempek culinary is in great demand among the people of South Sumatra and outside the region. Pempek culinary as icon of Palembang city, when people know pempek culinary they know Palembang city. The method used in this study is a qualitative descriptive method, where in this method there are several stages of data collection by means of interviews, observations, and documentation. The purpose of this study is to provide understanding/knowledge to the people of Palembang city that culinary can be an identity, heritage, and pride of the community. This can make pempek culinary an icon of the city of Palembang. space between lines.